Fuzzy logic controller based three phase shunt active power filter for harmonics reduction - Musa, S.; Mohd Radzi, Mohd Amran; Hizam, Hashim; Abdul Wahab, Noor Izzri (IEEE (IEEE Xplore), 2014)
Shunt active power filter is a complete current source which can provide a effective and adjustable solution for elimination of harmonic currents in power system. Its performance, depends on strategy employed in reference current generation, control technique and topology of inverter used in the design. In this study, fuzzy logic current control technique was presented for generation of pulse for PWM current control of the three phase inverter. A band pass filter was used in synchronous reference frame algorithm (SRF) for harmonics extraction. The shunt active power filter performance was evaluated with MATLAB/SIMULINK under balanced voltage condition. The result obtained gives good and satisfactory response to mitigate the harmonics in the system.